Socio-Demographic Status among Rural Municipalities in Humla District, Nepal: A Comparative Study - Khadka, Gopal (CHINTAN-DHARA, 2023)
This study compares the status of rural municipalities in the Humla district of Nepal regarding various household and demographic variables. This paper aims to compare rural municipalities of the Humla district in terms of population, area, sex ratio, literacy ratio, dependency ratio, fuel used, drinking water, internet user, etc. It is based on secondary data from the central bureau of statistics (CBS). The descriptive and comparative design is used to explore the result. It analyzes the data from the perspective of rural development. Rural development is the process of creating wellbeing and ensuring the quality of life among rural people. This study revealed that there are unequal situations in rural municipalities. In some rural municipalities, there is a situation of demographic loss. There is a lack of well-being among people. Deficiencies and deprivation of socio-economic requirements are common for them. Rural areas in the northern belt have acute problems compared to the south-eastern belt of the district. Three tiers of government along with market and cooperative sectors must focus to launch their policy and program to uplift the miserable situation of rural municipalities in Humla district.